THE ACEH BESAR DISTRICT GOVERNMENT’S POLICY ON THE FULFILLMENT OF DISABILITY RIGHTS IN THE ACEH BESAR DISTRICT SOCIAL SERVICE DEPARTMENT - Muhammad Abduh; Nasrul Zaman; M. Yani; Irwan Saputra; T Maulana (International Journal of Medical Science and Public Health Research, 2024)
The pursuit of social justice and equity is a fundamental aspect of governance, especially when addressing the needs of marginalized groups. In Aceh Besar Regency, the government has been tasked with ensuring that the rights and needs of persons with disabilities are met through various policies and programs. This research focuses on the fulfillment of social rights for persons with disabilities in Aceh Besar Regency, highlighting the role of the Social Service in supporting the welfare of this group. Geographically, Aceh Besar Regency covers an area of 290,350.73 hectares with a population of 383,477 as of 2020. The economy of this regency is dominated by the tertiary sector, followed by the primary and secondary sectors. The Aceh Besar Social Service is responsible for carrying out government affairs in the social sector, including rehabilitation, protection, and social empowerment. This study identifies several programs implemented by the Social Service, such as culinary skills training, handicrafts, and creativity festivals for persons with disabilities. However, the findings indicate that the existing programs have not fully met the needs of persons with disabilities, particularly in terms of improving welfare and economic sustainability. Budget constraints are identified as the main obstacle to the effective implementation of programs, including the provision of medical aids. This research underscores the need for increased funding allocation and the development of more inclusive and sustainable programs to ensure the fulfillment of the social rights of persons with disabilities in Aceh Besar.